Electrochemical polymer electrolyte membranes - Fang, Jianhua; Qiao, Jinli; Wilkinson, David P.; Zhang, Jiujun (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'Electrochemical Polymer Electrolyte Membranes' covers PEMs from fundamentals to applications, describing their structure, properties, characterization, synthesis, and use in electrochemical energy storage and solar energy conversion technologies. Featuring chapters authored by leading experts from academia and industry, this authoritative text discusses cutting-edge methodologies in PEM material selection and fabrication, points out important challenges in developing PEMs and recommends mitigation strategies to improve PEM performance, analyzes the current integration of PEMs with primary power devices and explores research trends for the next generation of PEMs. --
Chapter 1. Overview of electrochemical polymer electrolyte membranes / T. Leon Yu -- chapter 2. Perfluorinated polymer electrolyte membranes / Hong Li and Yongming Zhang -- chapter 3. Sulfonated polyimide membranes / Xinbing Chen -- chapter 4. Sulfonated poly(Ether Sulfone) membranes / Tomoyo Higashihara and Mitsuru Ueda -- chapter 5. Sulfonated poly(Ether Ketone) membranes / Chengji Zhao, Gang Zhang, and Hui Na -- chapter 6. Sulfonated polyphenylenes and the related copolymer membranes / Xuan Zhang and Shouwen Chen -- chapter 7. Polyphosphazene membranes / Jun Lin and Shaojian He -- chapter 8. Phosphoric acid-doped polybenzimidazole membranes for high-temperature proton exchange membrane fuel cells / Jianhua Fang and Xiaoxia Guo -- chapter 9. Hybrid/composite membranes / Yan Yin -- chapter 10. Aliphatic polymer electrolyte membranes / Jinli Qiao, Junkun Tang, and Yuyu Liu -- chapter 11. Aromatic polymer electrolyte membranes as hydroxide conductors / Zhaoxia Hu and Shouwen Chen -- chapter 12. Theoretical modeling of polymer electrolyte membranes / Su Zhou, Fenglai Pei, and Jeffrey De Lile.
Includes bibliographical references and index.
Keywords: Energy storage; Energy conversion; Polyelectrolytes